(untitled) (International Journal of Engineering and Computer Science, 2022)
Contemporary studies on the use of paved drying bed (PDB) indicate a decline in knowledge and technology-gap on the performance of this infrastructure. In consequence therefore, environmental pollution arising from untreated sludge is on the increase, especially in developing countries. In this work, model equation was developed with the existing data from field experiment using Polymath 5.1 software. The process parameters considered were temperature, relative humidity, wind speed, sun intensity and drying rate. The multiple linear regression results showed that wind speed optimised the response with the highest factor coefficient of 0.12. The developed model was well validated with a correlation coefficient of 0.97, thus could serve as a useful tool for sludge treatment plant operators in evaluation and assessment of the performance of PDB.